SOSIOLOGI HUKUM ISLAM: ILMU AL-IJTIMA'I LI SYARI'ATI AL-ISLAMIYYAH - Alfiandi Zikra; Faisar Ananda Arfa (AL-ILMU, 2023)
This paper aims to describe in general sociological Islamic law. from the presentation of the sociology of law and Islamic law, then with the sociology of Islamic law is a social science that studies legal phenomena that aims to provide an explanation of the practices of jurisprudence that regulate the reciprocal relationship between various kinds of social phenomena in Muslim society as creatures that adhere to Islamic law. Then Islam can be studied with various approaches. Therefore, the sociology of Islamic law is an understanding of juridical (Islamic law) towards societal problems, especially those embodied by Indonesian Islamic society by using principles and theories originating from Islamic concepts excavated from al-Qur'an sources. 'an and hadith Keywords: Sociology, Islam, Law, Shari'a and Hadith